Recent developments in the molecular biology of pain - Wollemann, Mária (Acta Biologica Szegediensis, 2011)
Research in understanding the molecular basis of pain has accelerated in the last twenty years. Beside the description of the ‘chemical soup’ and their receptors in chronic pain, the cloning and role of the TRP (Transient Receptor Potential) channels was also discovered, making the synthesis of new agonists and antagonists possible. However the organism itself is able to antagonize pain by activating endogenous opioid and cannabinoid receptors. New pathways in pain therapy might evolve by exploring these molecular mechanisms further.